Pengaruh Suhu Terhadap Tegangan Permukaan : Impikasi Praktikum Cookbook - Muhammad Ziddan Rachman; Zahra Aulia Alifa; Nawallaili Musyayaroh; Adam Malik (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
Surface tension is a critical physical property in various applications, yet the understanding of temperature effects on surface tension remains limited. This study aims to investigate the influence of temperature on the surface tension of water through laboratory experiments. The method includes measuring surface tension in hot and cold water using simple equipment. The results show significant variation in surface tension, with hot water exhibiting higher surface tension compared to cold water under certain conditions. These findings contradict the theory that increasing temperature should reduce surface tension. Factors such as measurement errors and water contamination likely affected the results. This study highlights the importance of developing stricter methodologies for surface tension measurements and provides essential insights for practical and educational applications.